Segundas nupcias: redefinición de los vínculos amorosos y de crianza - dos Santos Marcondes, Glaucia (El Colegio de México A.C., 2009)
The family dynamics and reproductive projects of second unions constitute the focus of this paper. This is qualitative study undertaken in Campinas (Brazil) on a group of 10 couples that have remarried. It analyzes the aspects that marked the respondents’ process of forming a family. The main findings include the fact that reconstituted families are forced to reformulate links with parents and the duties and rights of each of the players involved in a new family configuration. The existence of children from previous unions and the type of contact with them significantly affects domestic and family dynamics and the new couple’s desire to expand their family.